ENHANCING STUDENTS’ MOTIVATION: THE EFFECT OF A STRUCTURED ORAL EXAMINATION IN BASIC CLINICAL SKILLS TRAINING - Ratih Yulistika Utami; Oppi Mirzatillah; Desi Isnayanti; M. Jalaluddin Assuyuthi Chalil (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Basic Clinical Skills (BCS) is one of the learning methods in medical education that acts as an intermediary bridge to apply procedural knowledge and clinical competency for medical students. Medical educators have successfully used many ways to assess students’ abilities, both oral and written. Oral examinations have vast advantages compared to other assessment methods. However, no standardization of questions to be tested becomes an essential issue in the assessment process. A structured oral examination may increase students’ motivation to prepare themselves better to study the material before following BCS training. This study aimed to determine the effect of a structured oral examination on students’ motivation and identify students’ motivation. Methods: This quasi-experimental research used a pretest-posttest design to assess the effect of applying the structured oral examination on students’ motivation. The subject of this study was the third-year medical students that amounted to 109 students. Sample selection was made by total sampling. In this study, the authors used SMQ-II questionnaires to measure the students’ motivation. Results: This research showed significant differences between student motivation on pretest and posttest (p-value of 0,000) after the students were given the structured oral examination at the beginning of basic clinical skills training. It means the structured oral examination affected students’ motivation. Conclusion: The structured oral examination administered for students before entering BCS learning processes had a significant impact on the students’ motivation. The preparation and the regulation of the structured oral examination on the BCS learning processes should be reinforced to motivate the students and make them more skillful